Upaya Meningkatkan Perkembangan Kognitif Anak Melalui Kegiatan Mengenal Konsep Bilangan di TK Dharma Wanita 67 Pesucen - Hikmawati Hikmawati; Takasun Takasun; Rofiqoh Rofiqoh (Pascasarjana Universitas Mataram, 2022)
This community service activity is an effort to improve children's cognitive development through activities to recognize the concept of numbers in TK Dharma Wanita 67 Pesucen. Getting to know the concept of numbers in question is to use objects 1 to 10. The activity will be held on Wednesday, November 17, 2021, with a total of 7 students. The method of carrying out activities consists of initial, core, and final activities. Activities carried out in the early stages are welcoming children, structuring the playing environment, opening. Activities carried out at the core stage are observing, asking questions, gathering information, reasoning, communicating with various activities (recognizing the concept of numbers 1 to 10 by counting roses, Finger painting the shape of roses, Arranging roses). The activities carried out in the final stage are recalling and closing. The assessment rubric consists of four criteria, namely Undeveloped, Starting to Develop, Developing as Expected, and Developing Very Well. The results of observations indicate that the level of cognitive development of children is in the criteria of Developing According to Expectations. Efforts to improve children's cognitive development through activities to recognize the concept of numbers need to be continued so that the criteria increase to a better one